1987
DOI: 10.1111/j.1600-0536.1987.tb01445.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential immunophenotypic study of lymphoid infiltrate in allergic and irritant reactions

Abstract: Sequential biopsies (4-72 h) of early allergic and irritant patch test reactions have been examined immunohistologically for reactivity with 19 monoclonal antibodies against antigens on lymphoid cells in order to investigate the nature/origin of the infiltrating lymphoid cells and assess their state of activation/proliferation. The composition of the infiltrates was similar in allergic and irritant reactions and consisted of T-lymphocytes of helper/inducer types in association with T-cell accessory cells, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 13 publications
0
15
1
Order By: Relevance
“…60 A general feature of the inflammatory infiltrate in ACD is the high proportion of T-cells. 2,35,42,44 This characteristic has also been observed in porcine samples containing high numbers of CD2 ϩ , CD5 ϩ , CD4 ϩ , CD8 ϩ , and CD25 ϩ cells. The ratio of dermal CD2 ϩ and CD5 ϩ cells was similar to the epidermal condition and NK cells may have also been labeled with the anti-CD2 antibody MSA4.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…60 A general feature of the inflammatory infiltrate in ACD is the high proportion of T-cells. 2,35,42,44 This characteristic has also been observed in porcine samples containing high numbers of CD2 ϩ , CD5 ϩ , CD4 ϩ , CD8 ϩ , and CD25 ϩ cells. The ratio of dermal CD2 ϩ and CD5 ϩ cells was similar to the epidermal condition and NK cells may have also been labeled with the anti-CD2 antibody MSA4.…”
Section: Discussionmentioning
confidence: 63%
“…2 The antibody MIL2, which is reported to label monocytes, macrophages, and neutrophil granulocytes, did not react with aggregated inflammatory cells in the epidermis. Therefore, these cells may have lost their surface markers because of the onset of necrosis or autolysis within these intraepidermal microabscesses.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular source of mediators causing nociceptor sensitization in SLS reactions, as well as other human models of inflammatory pain, remains to be elucidated. Keratinocytes are likely the key source of cytokines in SLS and UVB-inflammation [6,27], but macroscopic and immunohistochemical studies have also revealed pronounced influxes of polymorphonuclear cells as well as lymphocytes at SLS sites [28][29][30]. There is likely to be a large overlap among key soluble pain-related mediators, including TNF-a, IL-1b, and IL-6, released by SLS, on one hand, and those mediators found to be upregulated in established human models of inflammatory dermal pain such as UVB-inflammation [27,[31][32][33][34] and thermal injuries, on the other [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…With increasing understanding of the cellular and molecular events of contact sensitivity, investigators have attempted to develop improved methods for differentially diagnosing contact allergic reactions from contact irritant reactions in humans. Most studies have investigated Langerhans cells (LC), T cells, and macrophages to determine differences in structure and phenotypic expression of markers in contact allergic reactions (Ferguson et al, 1985;Wood et al, 1986;Gawkrodger et al, 1986;Avnstorp et al, 1987;Mommaas et al, 1992). These studies have attempted to distinguish between allergic and irritant reactions to patch tests by using semiquantitative histological examination of skin biopsies.…”
Section: Differentiation Of Allergens and Irritants Using Flowmentioning
confidence: 99%